ヒガシ ナンキョク エンダビーランド リーセルラルセン サンロク ノ ガンセキ ヒョウガ - 三枝, 茂; サイグサ, シゲル; 三浦, 英樹; ミウラ, ヒデキ; 前杢, 英明; マエモク, ヒデアキ; 平川, 一臣; ヒラカワ, カズオミ; Saigusa, Shigeru; Miura, Hideki; Maemoku, Hideaki; Hirakawa, Kazuomi (1998)
P(論文) 東南極, エンダビーランドのリーセルラルセン山麓において従来山岳モレーンとして解釈されてきた地形の一部は, 風化程度の小さい安息角をなす前縁斜面と上部斜面の畝と溝を持つ微地形の存在および他の地域で報告されている現成の岩石氷河の縦断面形態との類似性から, 現成の岩石氷河であると考えられる。現地調査と空中写真判読から岩石氷河の可能性をもつ地形は, 崖錐の基部, 上部に大きな雪渓・氷河を持つモレーンの末端, およびカール底に集中して分布する傾向が明らかになった。これまで南極における現成の岩石氷河の記載は少なかったことから, 南極沿岸域の地形形成環境を明らかにする上で今後, 継続した気温・地温, 岩石氷河の流動に関する観測が望まれる。 Part of the debris slopes previously defined as alpine moraines at the foot of Mt. Riiser-Larsen were considered to be active rock glaciers in terms of longitudinal profiles, degree of weathering, size of surface boulders and morphological similarities with active rock glaciers in other regions. Possible rock glaciers tend to occur at the foot of talus, the bottom of cirques and the tips of moraines below snow patches and/or alpine glaciers. Descriptions of rock glaciers in Antarctica have so far been few. Continuous monitoring of the movement and thermal regime of rock glaciers will be necessary to understand geomorphic environments and processes in the Antarctic coastal regions. departmental bulletin paper